The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.jp.7211801
|View full text |Cite
|
Sign up to set email alerts
|

Cost, causes and rates of rehospitalization of preterm infants

Abstract: Objective: To examine hospital readmissions for premature infants during the first year of life.Study Design: The California maternal and newborn/infant hospital discharge records were examined for subsequent readmission during the first year of life for all newborns from 1992 to 2000. Discharge diagnoses, hospital days, demographic data and hospital charges for infants born preterm (<36 weeks gestation) were identified and evaluated.Result: About 15% of preterm infants required at least one rehospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
153
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 24 publications
(27 reference statements)
15
153
3
7
Order By: Relevance
“…Reduced gestational age is another well-known risk factor for respiratory infection-related re-hospitalisations during early life [39], with community-based studies reporting increasing cost, risk and severity of infection as gestational age decreases [5,40,45]. In one series, preterm infants born at less than 25 weeks’ gestation had more than twice the frequency of re-hospitalisation due to acute respiratory infections and more than twice the length of hospital admission compared to those born in the late preterm period (31% and 12 days vs. 13% and 5 days, respectively) [40].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Reduced gestational age is another well-known risk factor for respiratory infection-related re-hospitalisations during early life [39], with community-based studies reporting increasing cost, risk and severity of infection as gestational age decreases [5,40,45]. In one series, preterm infants born at less than 25 weeks’ gestation had more than twice the frequency of re-hospitalisation due to acute respiratory infections and more than twice the length of hospital admission compared to those born in the late preterm period (31% and 12 days vs. 13% and 5 days, respectively) [40].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…In one series, preterm infants born at less than 25 weeks’ gestation had more than twice the frequency of re-hospitalisation due to acute respiratory infections and more than twice the length of hospital admission compared to those born in the late preterm period (31% and 12 days vs. 13% and 5 days, respectively) [40]. More recent analysis from a large population based, data-linkage study reported a 12% increase in the overall frequency of infection-related hospitalisation during childhood for each week reduction in gestational age [6].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Though morbidity is most concerning with early preterm births, studies have reported increased rates of neonatal medical problems and increased hospital costs both at delivery and for readmission in the first year of life for premature infants born between 35 and 37 weeks of age (late preterm birth) (2)(3)(4). Greater understanding of potential mechanisms involved in prematurity would be beneficial in decreasing infant morbidity as well as major medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies across the world have tried to ascertain the neonatal risk factor for post NICU discharge hospital re-admission [1][2][3][8][9][10][11][12][13]. Ambalavanan, et al in their recent publication using classification and regression tree analysis concluded that neonates who spent > 120 days during their NICU admission for pulmonary reasons had a 66% re-hospitalization rate compared to 42% without such stay [3].…”
Section: Risk Factors For Hospital Re-admissionmentioning
confidence: 99%
“…Re-hospitalization after initial discharge from NICU for preterm infants has been examined in various settings across the world [1][2][3][4][5][6][7][8][9][10][11][12][13]. Reasons for re-hospitalizations in extreme preterm infants can be related either to medical (bronchiolitis, lower-respiratory tract infection, asthma, reflux disease) or to surgical (PEG related problems, V-P shunt related issues, hernia repair) causes.…”
Section: Introductionmentioning
confidence: 99%